Factors Affecting The Implementation of SAK EMKM In MSMEs with Environmental Uncertainty as Moderation Variable - Daniyah, Wati; Tarmidi, Deden (Devotion : Journal of Research and Community Service, 2023)
This study aims to examine the effect of educational background, understanding of accounting and understanding of information technology on the implementation of SAK EMKM in SMEs with environmental uncertainty as a moderation. The population in this study was 11,746 SMEs in Tangerang City and a sample of 99 SMEs was obtained by calculating using the Slovin formula. Research data collection was carried out by distributing questionnaires to the 99 SMEs. Testing the data in this study was carried out using Partial Least Squares (PLS). The results of this study indicate that educational background has a significant effect on the implementation of SAK EMKM in Tangerang SMEs, while accounting understanding and understanding of information technology have no significant effect on the implementation of EMKM SAK in Tangerang City SMEs. Meanwhile, environmental uncertainty moderates the effect of educational background, understanding of accounting, and understanding of information technology on the implementation of SAK EMKM in SMEs in Tangerang.